Comparison of bolus versus continuous infusion of propofol for procedural sedation: a meta-analysis. (2nd November 2017) - Choi, Geun Joo; Kang, Hyun; Baek, Chong Wha; Jung, Yong Hun; Lee, Je Jin
Abstract: Objective: To compare the efficacy and safety of bolus infusion versus continuous infusion for propofol sedation. Methods: We searched OVID-MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Google Scholar, Koreamed, and Kmbase databases to identify all randomized controlled trials that compared bolus infusion with continuous infusion for propofol sedation. We evaluated propofol dose used, procedure, sedation, and recovery time. The incidences of respiratory and cardiovascular complications were also evaluated. Results: A total of 12 studies of 963 patients were included. The required propofol dose was significantly higher in continuous infusion compared with bolus infusion (standardized mean difference [SMD]: −0.44; 95% confidence interval [CI]: −0.71 to −0.16; I 2  = 84%). Sedation time was significantly longer in continuous infusion compared with bolus infusion (mean difference [MD]: −8.58 min; 95% CI: −15.13 to −2.03; I 2  = 44%). The recovery time and incidences of desaturation, airway intervention, hypotension, and bradycardia were comparable between bolus and continuous infusion. Conclusions: Propofol sedation by continuous infusion required a higher dose of propofol compared with bolus infusion, but the recovery time and frequency of complications were similar.